Behavioral metabolomics analysis identifies novel neurochemical signatures in methamphetamine sensitization. (30th September 2013) - Adkins, D. E.; McClay, J. L.; Vunck, S. A.; Batman, A. M.; Vann, R. E.; Clark, S. L.; Souza, R. P.; Crowley, J. J.; Sullivan, P. F.; van den Oord, E. J. C. G.; Beardsley, P. M.
Abstract : Behavioral sensitization has been widely studied in animal models and is theorized to reflect neural modifications associated with human psychostimulant addiction. While the mesolimbic dopaminergic pathway is known to play a role, the neurochemical mechanisms underlying behavioral sensitization remain incompletely understood. In this study, we conducted the first metabolomics analysis to globally characterize neurochemical differences associated with behavioral sensitization. Methamphetamine (MA)‐induced sensitization measures were generated by statistically modeling longitudinal activity data for eight inbred strains of mice. Subsequent to behavioral testing, nontargeted liquid and gas chromatography–mass spectrometry profiling was performed on 48 brain samples, yielding 301 metabolite levels per sample after quality control. Association testing between metabolite levels and three primary dimensions of behavioral sensitization (total distance, stereotypy and margin time) showed four robust, significant associations at a stringent metabolome‐wide significance threshold (false discovery rate, FDR <0.05). Results implicated homocarnosine, a dipeptide of GABA and histidine, in total distance sensitization, GABA metabolite 4‐guanidinobutanoate and pantothenate in stereotypy sensitization, and myo‐inositol in margin time sensitization. Secondary analyses indicated that these associations were independent of concurrent MA levels and, with the exception of the myo‐inositol association, suggest a mechanism whereby strain‐based genetic variation produces specific baseline neurochemical differences that substantially influence the magnitude of MA‐induced sensitization. These findings demonstrate the utility of mouse metabolomics for identifying novel biomarkers, and developing more comprehensive neurochemical models, of psychostimulant sensitization . Abstract : Homocarnosine, pantothenate, 4‐guanidinobutanoate and myo‐inositol were robustly associated with methamphetamine sensitization.